Psychomotor, Functional, and Cognitive Profiles in Older People with and without Dementia:What Connections?. (May 2019) - Morais, Ana; Santos, Sofia; Lebre, Paula
Background: In typical aging, it is possible to observe a decline in psychomotor domains, such as balance or global and fine motor skills as well as a cognitive and functional decline. Although, it is not clear which psychomotor domains are mostly affected in elderly with dementia and the association with the cognitive and functional level. Objective: To identify the correlation between psychomotor, cognitive, and functional skills, and seeking whether there are differences among persons with and without dementia. Design and Methods: A total of 120 persons with dementia (ages between 61 and 99 years old; mean age 80.6 ± 7.4) and 377 persons without dementia (ages between 60 and 99 years old; mean age 77.2 ± 8.7) were recruited from nursing homes, day-care centers, and home care. Consenting participants were assessed in psychomotor, cognitive, and functional domains using the Mini Mental State Examination (MMSE) to assess cognitive impairment, the Barthel Index (BI), and Lawton Index (LI) to identify basic and instrumental activities of daily living and a Portuguese Version of Éxamen Geronto-Psychomoteur (P-EGP) to evaluate psychomotor skills. Results: People with dementia showed a higher percentage of cognitive deficit and higher level of dependency in basic and instrumental activities of daily living. Further, findings also showed significant differences in psychomotor domains and total of P-EGP, with exception of Joint Mobilizations of Upper and Lower Limbs. There were moderate to strong correlations between the totals of the scales, and between the totals and domains. Conclusions: The population with dementia has higher percentage of cognitive deficit, higher dependency on the performance of basic and instrumental activities of daily living and poorer psychomotor performance, except in joint mobilizations. It was also possible to find strong correlations between the total of P-EGP and the total of cognitive and functional scales. Implications for future research and practice are discussed.